Two‐year follow‐up of a randomized multicenter study comparing a drug‐coated balloon with a drug‐eluting stent in native small coronary vessels: The RESTORE Small Vessel Disease China trial. (13th January 2020) - Tian, Jian; Tang, Yi‐da; Qiao, Shubin; Su, Xi; Chen, Yundai; Jin, Zening; Chen, Hui; Xu, Biao; Kong, Xiangqing; Pang, Wenyue; Liu, Yong; Yu, Zaixin; et al.
Abstract: Objectives: To report the clinical outcomes of the RESTORE drug‐coated balloon (DCB; Cardionovum, Bonn, Germany) for treatment of de novo small vessel disease (SVD) beyond 1 year. Background: Previous reports have demonstrated the noninferiority of the RESTORE DCB to the RESOLUTE Integrity drug‐eluting stent (DES; Medtronic, Minneapolis, Minnesota) in terms of 9‐month in‐segment percent diameter stenosis. Methods: In the prospective, multicenter, noninferiority RESTORE SVD China trial, 230 patients with visually‐estimated reference vessel diameter (RVD) ≥2.25 and ≤2.75 mm were randomized to DCB or DES in a 1:1 ratio stratified by diabetes and number of lesions treated. Furthermore, 32 patients with RVD ≥2.00 and <2.25 mm were enrolled in a nested very small vessel (VSV) registry. Clinical follow‐up were performed at 2 years to evaluate target lesion failure (TLF) in both groups and the VSV cohort. Results: Overall, 256 (97.7%) patients (115 and 109 in the DCB and DES groups, respectively, and 32 in the VSV cohort) completed 2 years of follow‐up. There was no significant difference in TLF between the DCB and DES groups (5.2 vs. 3.7%, p = .75). Target lesion revascularization was acceptable at 1 month, 1 year, and 2 years, and did not differ significantly with DCB from that in the DES group (0.9 vs. 0%, p = 1.0, 4.4 vs. 2.6%, p = .72, 5.2 vs. 2.8%, p = .50, respectively). Conclusions: Compared to the second‐generation DES, the RESTORE DCB did not increase the risk of clinical outcomes. Late catch‐up phenomen requiring revascularization was not significant in this study.